Getting Started Creating Data Dictionaries: How to Create a Shareable Data Set. Issue 1 (February 2021) - Buchanan, Erin M.; Crain, Sarah E.; Cunningham, Ari L.; Johnson, Hannah R.; Stash, Hannah; Papadatou-Pastou, Marietta; Isager, Peder M.; Carlsson, Rickard; Aczel, Balazs
As researchers embrace open and transparent data sharing, they will need to provide information about their data that effectively helps others understand their data sets' contents. Without proper documentation, data stored in online repositories such as OSF will often be rendered unfindable and unreadable by other researchers and indexing search engines. Data dictionaries and codebooks provide a wealth of information about variables, data collection, and other important facets of a data set. This information, called metadata, provides key insights into how the data might be further used in research and facilitates search-engine indexing to reach a broader audience of interested parties. This Tutorial first explains terminology and standards relevant to data dictionaries and codebooks. Accompanying information on OSF presents a guided workflow of the entire process from source data (e.g., survey answers on Qualtrics) to an openly shared data set accompanied by a data dictionary or codebook that follows an agreed-upon standard. Finally, we discuss freely available Web applications to assist this process of ensuring that psychology data are findable, accessible, interoperable, and reusable.